On mean throughput of one-processor systems - Chefranov, A. G.; Chefranov, A. A. (IEEE, 2006)
A simple formula for calculation of a throughput of a one-processor system with a batch processing is obtained. It is shown that a throughput is maximized by algorithm SPT. A relation between a mean response (turnaround) time and a throughput is discussed.
IEEE-TTTC International Conference on Automation, Quality and Testing, Robotics -- MAY 25-28, 2006 -- Cluj Napoca, ROMANIA